Asthma severity at night during recovery from an acute asthmatic attack. Issue 10 (October 1991) - Hoskyns, E W; Heaton, D M; Beardsmore, C S; Simpson, H
Abstract : This study was undertaken to investigate the severity of night time asthma in children in hospital recovering from an acute attack of asthma. Twenty two children aged 5-14 years were studied. Coughing 'epochs' overnight varied from one to 156 (median 39.5) and mean overnight arterial oxygen saturation (Sao2) from 82 to 98% (mean 91.3). Log values for cough showed a correlation with Sao2. An Sao2 of less than 90% was invariably associated with coughing but Sao2 above 95% did not preclude cough. Peak flow measured in the morning or evening correlated with Sao2 but not with log cough, and clinical examination scores showed no correlation with overnight measurements. Night time Sao2 correlated better with daytime tests of lung function than log cough. In general, night time indices of severity reflected daytime pulmonary function status but night cough was sometimes prominent in less severely affected cases. At the time of discharge, clinical indices of severity underestimated the degree of functional impairment at night.